Antibacterial Effects of Garlic Ethyl Acetate Fraction (Allium Sativum L.) on the Growth Of Bacteria Staphylococcus aureus and Escherichia coli - Juninda, Larasati; Dewi, Listiana Masyita; Sintowati, Retno; Bestari, Rochmadina Suci (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background: Antibiotics are a treatment used to treat bacterial infections. However, the many antibiotic-resistant bacteria caused researchers to use plants as an alternative treatment, one of which is garlic (Allium sativum L.).Objective: Previous research stated that the diameter of the inhibition zone by garlic had a more excellent value than the antibiotics used. Hence, the researchers were interested in conducting an antibacterial test of the ethyl acetate fraction of garlic against the growth of Staphylococcus aureus and Escherichia coli.Methods: This study was an experimental laboratory using the posttest-only control group design method in the Kruskal Wallis test data analysis.Results: the results of the inhibition analysis with p-value < 0.05 in each test group for both Staphylococcus aureus and Escherichia coli. With the Mann-Whitney test, the results obtained a p-value <0.005 for each bacteria and test group. The most significant value, namely p= 0.002. This result shows significant differences between the test groups for each bacterium.Conclusion: There is an antibacterial effect of the ethyl acetate fraction of garlic (Allium sativum L.) at concentrations of 25%, 50%, and 100% against the growth of Staphylococcus aureus and Escherichia coli